2015
DOI: 10.1039/c4dt03554b
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a Ni salen complex in zeolite Y: an experimental and DFT study

Abstract: It is observed that for a square planar Ni(II)-Schiff base complex of the general formula {Ni(II)L}, where L is {L: N,N'-bis(5-hydroxy-salicylidene)ethylenediamine}, when encapsulated in a supercage of zeolite Y the bulky guest complex adopts a non-planar geometry without disturbing the integrity of the zeolite framework. Detailed comparative characterization is carried out to understand the structural change of the guest complex as a result of steric and electronic interactions with the host framework. UV-Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 57 publications
5
34
0
Order By: Relevance
“…It is quite interesting to perceive a regular blue shift and intensification of the d‐d transitions in the encapsulated copper ‐ Schiff‐base complexes. Such behavior already has been observed in the zeolite Y encapsulated complexes . Observed modified electronic behavior in the d‐d region is certainly an effect of different geometry of the co‐ordination sphere, which the guest complex has adopted under the space restrictions of host supercage.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…It is quite interesting to perceive a regular blue shift and intensification of the d‐d transitions in the encapsulated copper ‐ Schiff‐base complexes. Such behavior already has been observed in the zeolite Y encapsulated complexes . Observed modified electronic behavior in the d‐d region is certainly an effect of different geometry of the co‐ordination sphere, which the guest complex has adopted under the space restrictions of host supercage.…”
Section: Resultsmentioning
confidence: 53%
“…Scanning electron microscopy also supports the fact that the complex formation is primarily taking place inside the host cavities. From the SEM images (SEM micrographs given in Figure a‐c before Soxhlet extraction for CuS4‐Y with different resolution; Figure d‐f for CuS4‐Y and Figure g‐i for CuSp4‐Y after Soxhlet extraction and Figure S4 in supporting information for CuS1‐Y and CuSp1‐Y), it is observed that before Soxhlet extraction, there are some detectable surface species probably due to the formation of the complex at the surface or un‐reacted ligands, however, are disappeared after Soxhlet extraction . making zeolite particle boundaries more clearly visible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations